2021
DOI: 10.33474/jp2m.v1i4.8691
|View full text |Cite
|
Sign up to set email alerts
|

Sosialisasi Digital Marketing Dan Inovasi Produk Pada UKM Gula Merah Guna Mempertahankan Ekonomi Di Masa Pandemi Covid-19

Abstract: Berbagai permasalahan terkait menurunnya ekonomi UKM pada masa pandemi covid-19 saat ini memberikan dampak yang cukup signifikan bagi para pelaku UKM. Salah satu UKM yang terkena imbas pandemi adalah UKM pembuat gula merah di Desa Sarongan, Kecamatan Pesanggaran, Kabupaten Banyuwangi yang mengalami penurunan pendapatan. Puluhan atau ratusan masyarakat mendapatkan penghasilan dari memproduksi gula merah tersebut dan lalu menjualnya kepada pengepul. Untuk menstabilkan penjualan dan penghasilan masyarakat, kami m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
0
0
0
4
Order By: Relevance
“…Here we can see that the method is considered very appropriate during the Covid-19 pandemic, which demands various things must keep working by minimizing a direct physical touch (Winarti, 2021). Previous studies from (Dewi Diah Fakhriyyah, Yuni Wulandari, 2020) on the "Digital Marketing Socialization and Product Innovation in Brown Sugar SMEs to Maintain the Economy in the Covid-19 Pandemic, it was concluded that the influence of product innovation on the brown sugar SMEs to maintain the economy during the Covid-19 pandemic was significantly positive. Previous studies (Triandra et al, 2019) on the "Analysis of the Effect of E-Commerce on Improving the Performance of MSMEs in Sumbawa Regency", it is concluded that E-commerce affects the performance of MSMEs in Sumbawa Regency with a positive significance.…”
Section: Introductionmentioning
confidence: 64%
“…Here we can see that the method is considered very appropriate during the Covid-19 pandemic, which demands various things must keep working by minimizing a direct physical touch (Winarti, 2021). Previous studies from (Dewi Diah Fakhriyyah, Yuni Wulandari, 2020) on the "Digital Marketing Socialization and Product Innovation in Brown Sugar SMEs to Maintain the Economy in the Covid-19 Pandemic, it was concluded that the influence of product innovation on the brown sugar SMEs to maintain the economy during the Covid-19 pandemic was significantly positive. Previous studies (Triandra et al, 2019) on the "Analysis of the Effect of E-Commerce on Improving the Performance of MSMEs in Sumbawa Regency", it is concluded that E-commerce affects the performance of MSMEs in Sumbawa Regency with a positive significance.…”
Section: Introductionmentioning
confidence: 64%
“…Pendapatan masyarakat mengalami penurunan tajam antara 30-70% sedangkan pengeluaran tetap pada masa pandemic (Kurniasih, 2020). Pembatasan skala besar pada masa pandemi Covid-19 merupakan kendala yang cukup besar dikarenakan usaha-usaha kecil masyarakat masih melakukan transaksi secara tradisional, aktivitas jual beli menjadi terhenti dan terhambat di sektor distribusinya (Fakhriyyah et al, 2021).…”
Section: Pendahuluanunclassified
“…Berdasarkan jurnal penelitian (Fakhriyyah et al, 2020) mengatakan inovasi produk dilakukan dengan tujuan sebagai penambah nilai jual pada suatu produk agar penjualan produk tersebut dapat stabil dan pada akhirnya diharapkan dapat meningkatkan pendapatan. Menurut (T. Handayani & Tanjung, 2017) mengartikan inovasi sebagai kreatifitas dalam rangka memecahkan persoalan atau menciptakan peluang untuk menvapai keberhasilan.…”
Section: Inovasiunclassified